2023
DOI: 10.3389/fpls.2023.1142840
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling and gene expression analysis reveal the quality deterioration of postharvest toon buds between two different storage temperatures

Abstract: Toon buds, a popular woody vegetable, contain large amounts of nutrients. However, toon buds have strong respiratory metabolism after harvest and are highly prone to decay, resulting in quality deterioration. Low temperature can effectively inhibit postharvest senescence of toon buds. GC-TOF-MS combined with quantitative real-time PCR was used to elucidate the toon bud deterioration mechanism after harvest by analyzing the difference in the relative contents of primary metabolites and their derivatives, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It is well-known that the composition and content of chemical components of Chinese herbs change with soil conditions, cultivation measures and climate factors in the growth process [ 21 , 22 , 23 , 24 , 25 ]. In addition, relevant studies have shown that the primary processing, storage time and storage method of TCMs also affect the quality of Chinese herbs [ 26 , 27 , 28 , 29 , 30 ]. This may help to explain why the correlation coefficients for the samples from different origins, storage time and kneading processing in our investigation varied.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that the composition and content of chemical components of Chinese herbs change with soil conditions, cultivation measures and climate factors in the growth process [ 21 , 22 , 23 , 24 , 25 ]. In addition, relevant studies have shown that the primary processing, storage time and storage method of TCMs also affect the quality of Chinese herbs [ 26 , 27 , 28 , 29 , 30 ]. This may help to explain why the correlation coefficients for the samples from different origins, storage time and kneading processing in our investigation varied.…”
Section: Resultsmentioning
confidence: 99%